Pengaruh Model Pembelajaran Discovery Learning Berkonteks STEM Terhadap Kemampuan Siswa Memecahkan Masalah pada Materi Sifat Koligatif Larutan - Sitti Nurhalizah Dunggio; Astin Lukum; Lukman A.R Laliyo; Masrid Pikoli; Ahmad Kadir Kilo; Mangara Sihaloho (Universitas Negeri Gorontalo, 2026)
This study aimed to examine the influence of the discovery learning model in the STEM context on students’ problem-solving skills in the colligative properties of solution material in grade XII of SMA Negeri 4 Gorontalo. The data used in this study resulted from students’ problem-solving skills. Based on analysis, the avarage score of students’ critical thinking skills was obtained with a tcount value of 11.13 and a ttable value of 1.67065 (tcount ttable), which indicated that H0 was rejected and H1 was confirmed. In conclusion, the Discovery Learning Model influences students’ problem-solving skills in the colligative properties of solution material in the context of STEM.